2020
DOI: 10.2991/chi.d.200410.001
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of R-CHOP Versus Dose-Adjusted R-EPOCH in Treatment of Diffuse Large B-Cell Lymphoma with High-Risk Features

Abstract: Dose-adjusted rituximab, etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin (DA.R-EPOCH) is used for upfront treatment of high-risk diffuse large B cell lymphoma (DLBCL). In this study, we compared the outcomes in patients with high-risk DLBCL who received frontline rituximab, cycophosphamide, doxorubicin, vincristine, prednisone (R-CHOP) or DA.R-EPOCH immunochemotherapy. Outcomes and treatment-related cost were analyzed. DLBCL with one of the following features were included in the study: MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…17 Another study showed that, longitudinal cohort of 80 patients with high-risk DLBCL, 52 (65%) were treated with R-CHOP and 28 (35%) received DA-R-EPOCH.Most patients (71%) were e"60 years of age. 18 In this study, most patients had stage III or IV disease, 70.0% in R-CHOP group and 67% in R-DA-EPOCH group. Another study described that most of the patients had stage III or IV disease (74.0%).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…17 Another study showed that, longitudinal cohort of 80 patients with high-risk DLBCL, 52 (65%) were treated with R-CHOP and 28 (35%) received DA-R-EPOCH.Most patients (71%) were e"60 years of age. 18 In this study, most patients had stage III or IV disease, 70.0% in R-CHOP group and 67% in R-DA-EPOCH group. Another study described that most of the patients had stage III or IV disease (74.0%).…”
Section: Discussionmentioning
confidence: 53%
“…It was described in another study that that,86.1% of their patients had IPI score of less than 4 in R-CHOP group and 79.2% of patients in R-DA-EPOCH group. 18 In this study, all six chemotherapy cycles were completed by 90.0% of the R-CHOP and 78.0% of the DA-EPOCH-R group. Reasons for early discontinuation included disease progression (R-DA-EPOCH, 10%).…”
Section: Discussionmentioning
confidence: 86%
“…In terms of age, 19.0% of patients (n = 93) were at least 70 years old and 2.6% (n = 13) were 80 years or older. 17 Another study described that,longitudinal cohort of 80 patients with high-risk DLBCL,52 (65%) were treated with R-CHOP and 28 (35%) received DA.REPOCH. Most patients (71%) were e"60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study described that most of the patients had stage III or IV disease (74.0%). 17 Another study described that, on retrospective analysis, treatment of patients with high-risk DLBCL with DA.R-EPOCH resulted in similar clinical outcomes, but was associated with increased incidence of grade 3/4 neutropenia and need for transfusions during treatment when compared to those receiving R-CHOP regimen. 19 The more intensive, infusional DA-EPOCH-R was more toxic and did not improve progression free survival (PFS) or overall survival (OS) compared with R-CHOP.…”
Section: Discussionmentioning
confidence: 99%
“…In this new issue of Clinical Hematology International , you will read some high-level clinical reviews [ 2 , 3 ] and original reports [ 4 5 ], in addition to a diverse set of material. We hope you will continue to enjoy the IACH activities.…”
mentioning
confidence: 99%